2022
DOI: 10.3390/ani12091064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella spp. and E. coli Strains Isolated from Wild Carnivores in Janos Biosphere Reserve, Mexico

Abstract: Enterobacteriaceae are considered one the most important zoonotic pathogens. In this study, we analyzed the characteristics of E. coli and Salmonella spp. strains present in carnivores from Janos Biosphere Reserve, Mexico. These microorganisms had been isolated from a wide range of domestic and free-range animals, including wild carnivores. Fifty-five individuals were sampled, and the presence of Salmonella and E. coli was determined by bacteriological standard methods. Strains isolated were characterized by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The most frequently observed species were Didelphis albiventris (95), Necromys lasiurus (68), Calomys expulsus (62), Cerradomys vivoi (44), Marmosops incanus (39), Hylaeamys seuanezi (32), Gracilinanus agilis (31), Rhipidomys mastacalis (23), Wiedomys pyrrhorhinos (23), Leontopithecus chrysomelas (21), Turdus leucomelas (18), Thrichomys aff laurentius (18), Marmosa murina (16), Turdus rufiventris (13), Ceratopipra rubrocapilla (12), Bradypus torquatus (11), Coleodactylus meridionalis (11), Dixiphia pipra (9), Xiphorhynchus fuscus (8), Oligoryzomys nigripes (8), Trinomys albispinus (8), Dendrocincla turdina (7), Manacus manacus (7), Mus musculus (7), Oligoryzomys stramineus (7), Machaeropterus regulus (6) Cryptonanus agricolai (6), Leptotila rufaxilla (5), Glyphorynchus spirurus (4), Trinomys sp (4), and Monodelphis americana (3). Other species, which were represented by fewer than 2 exemplars each or were not identified, were grouped as others (48) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently observed species were Didelphis albiventris (95), Necromys lasiurus (68), Calomys expulsus (62), Cerradomys vivoi (44), Marmosops incanus (39), Hylaeamys seuanezi (32), Gracilinanus agilis (31), Rhipidomys mastacalis (23), Wiedomys pyrrhorhinos (23), Leontopithecus chrysomelas (21), Turdus leucomelas (18), Thrichomys aff laurentius (18), Marmosa murina (16), Turdus rufiventris (13), Ceratopipra rubrocapilla (12), Bradypus torquatus (11), Coleodactylus meridionalis (11), Dixiphia pipra (9), Xiphorhynchus fuscus (8), Oligoryzomys nigripes (8), Trinomys albispinus (8), Dendrocincla turdina (7), Manacus manacus (7), Mus musculus (7), Oligoryzomys stramineus (7), Machaeropterus regulus (6) Cryptonanus agricolai (6), Leptotila rufaxilla (5), Glyphorynchus spirurus (4), Trinomys sp (4), and Monodelphis americana (3). Other species, which were represented by fewer than 2 exemplars each or were not identified, were grouped as others (48) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Contact with wild fauna can increase the occurrence and/or incidence of pathogens both unidirectionally and bidirectionally [ 5 ], allowing organisms limited to certain areas and species to be transported to others [ 6 ]. This relationship intensifies if commercial animal breeding sites are located close to forested areas, as this promotes the sharing of food, water, and shelter [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified Salmonella spp. from wild animals, including badgers, wild boars, and coyotes [ 48 , 93 , 94 ]. In this study, wild leopard cats and badgers had the highest frequency of Salmonella spp ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%